Core-shell structure aerogel, preparation method thereof and application of core-shell structure aerogel in refractory bricks

By preparing core-shell structured silica/zirconia composite aerogels, the problems of structural collapse and loss of thermal insulation performance of silica aerogels at high temperatures were solved, achieving high strength and low thermal conductivity of refractory bricks, suitable for thermal insulation and protection of industrial kilns.

CN119430957AActive Publication Date: 2025-02-14ANHUI POLYTECHNIC UNIV

Patent Information

Application Number
CN202411340279.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-02-14
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

Existing silica aerogels have poor heat resistance and low strength, making them unsuitable for use in high-temperature environments in industrial kilns, and they cannot be blended with refractory brick raw materials for molding.

Method used

A core-shell structured silica/zirconia composite aerogel was prepared by hydrolyzing carboxylated silica aerogel with zirconium oxychloride to form a core-shell structure, combined with supercritical CO2 drying and organic solvent filling. The resulting aerogel was then uniformly mixed with refractory brick raw materials and fired at high temperature.

Benefits of technology

The prepared refractory bricks have high strength, high temperature resistance and low thermal conductivity, which solves the problems of structural collapse and loss of thermal insulation performance of traditional aerogels at high temperatures, and achieves both high thermal insulation and mechanical strength of refractory bricks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430957A_ABST
    Figure CN119430957A_ABST
Patent Text Reader

Abstract

The invention discloses a core-shell structure aerogel and a preparation method and application thereof in refractory bricks, and belongs to the technical field of thermal insulation materials, and the preparation method comprises the following steps: adding zirconium oxychloride into an ethanol water solution at room temperature for hydrolysis, then adding carboxylated silicon dioxide aerogel, stirring and mixing, then adding a gelling agent to form a sol solution, and carrying out vacuum drying to obtain the core-shell structure aerogel. Performing sealed aging to obtain wet gel, and performing solvent replacement, supercritical drying and crushing to obtain core-shell structure aerogel; the method for applying the aerogel to the refractory brick comprises the following steps: adding the aerogel with the core-shell structure into an organic solvent for soaking, then adding the refractory brick raw materials with the particle size of 0.05-0.2 mm for mixing, then adding the refractory brick raw materials with the remaining particle size for mixing, and finally adding a bentonite solution for uniformly mixing to obtain a refractory brick mixture; and carrying out compression molding, high-temperature calcination and cooling to obtain the refractory brick. The prepared refractory brick has the characteristics of high strength, high temperature resistance and low heat conductivity, and the problem that the strength and heat insulation of a traditional refractory brick cannot be considered at the same time is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal insulation materials, and in particular relates to a core-shell structure aerogel and a preparation method thereof and application in refractory bricks. Background Art

[0002] As one of the insulation materials for industrial kilns, refractory bricks not only have to resist erosion and friction of materials in the kiln, but also have to take into account the important functions of heat insulation, thermal insulation and protection of the kiln carcass. Therefore, the development of high-strength and low-thermal conductivity refractory bricks is conducive to reducing heat loss, extending the service life of the carcass, greatly reducing the fuel supply required for industrial kilns, and reducing standard coal consumption, which is of great significance to the company's carbon reduction and economic benefits. When the prior art improves refractory bricks, the prior art mainly improves refractory bricks in the following ways: 1. Multi-layer composite structure constructs low thermal conductivity refractory bricks. The utility model patent with publication number CN211977551 U discloses a new type of spinel brick for cement rotary kiln, and proposes a new structure in which a working layer, a thermal insulation layer and a heat insulating layer are composited layer by layer. However, the thermal expansion coefficients of the materials of each layer of the structure are quite different, which can easily cause high-temperature thermal shock material fracture, so its flexural strength is lost more than that of traditional thermal insulation materials; 2. Introducing lightweight aggregates. The invention patent with publication number CN116803956A discloses a method for preparing low thermal conductivity aluminum-silicon porous structure refractory bricks. The invention introduces thermal insulation lightweight aggregates, uses a mullite working layer to coat the lightweight aggregates, and then pours the mixed aggregates into a mold for drying and calcining to prepare new refractory bricks; although the introduction of lightweight aggregates can increase the heat transfer path and reduce the speed of heat transfer to the outside, the wear resistance and strength of the product are poor. Therefore, how to balance the compressive strength and low thermal conductivity of refractory bricks is a technical problem that needs to be solved urgently.

[0003] Silica aerogel has low density, light weight, large specific surface area, and ultra-low thermal conductivity, and is widely used in aerospace, military and other fields. With the breakthrough of low-cost silica aerogel technology, its application in the field of civil building insulation is becoming more and more extensive, so it is feasible to apply silica aerogel to refractory bricks. However, the heat resistance temperature of existing silica aerogel is only about 650°C. At higher temperatures, the pore structure of silica aerogel will undergo crystal transformation and collapse, resulting in a significant reduction in thermal insulation performance. It cannot meet the application scenario of industrial kiln production temperature of about 1300°C. Therefore, it is impossible to directly blend the existing silica aerogel with refractory brick raw materials and calcine them as a whole. It is necessary to further improve the existing silica aerogel to improve its compressive strength, heat resistance and reduce its thermal conductivity. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a core-shell structure aerogel to solve the problems of poor heat resistance and low strength of the silica aerogel mentioned in the background technology.

[0005] Another object of the present invention is to provide a core-shell structured silica and zirconium dioxide composite aerogel having higher heat resistance, strength and thermal insulation performance.

[0006] Another object of the present invention is to provide an application of a core-shell structure aerogel in refractory bricks.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A method for preparing a core-shell structure aerogel comprises the following steps:

[0009] Zirconium oxychloride is added to an ethanol aqueous solution at room temperature to completely hydrolyze into a uniform solution, and then carboxylated silica aerogel is added and stirred for 2-10 hours to evenly disperse the silica aerogel, and then a gelling agent is added to form a sol solution. After sealed aging, a wet gel is obtained, and then the wet gel is submerged with n-hexane to perform solvent replacement on the wet gel for 3-5 times, and then supercritical CO2 drying is performed and crushed to obtain a core-shell structure aerogel.

[0010] Furthermore, the mass ratio of the zirconium oxychloride, ethanol aqueous solution, carboxylated silica aerogel and gelling agent is 1:5-6:4-5:0.5-1; the concentration of the ethanol aqueous solution is 97wt%; and the gelling agent is propylene oxide or citric acid.

[0011] Furthermore, the carboxylated silica aerogel is prepared by the following steps:

[0012] γ-aminopropyltriethoxysilane and succinic anhydride were added to N,N-dimethylformamide and stirred and mixed, and stirred and reacted for 8-10 hours at room temperature under nitrogen protection, and then the calcined silica aerogel and deionized water were added and stirred and dispersed, and the stirring reaction was continued for 5-6 hours at room temperature, and carboxylated silica aerogel was obtained after centrifugal separation, washing with anhydrous ethanol, and drying. The amino group of γ-aminopropyltriethoxysilane reacted with succinic anhydride at room temperature to obtain siloxane containing carboxyl groups, and then the carboxyl groups were grafted onto the surface of silica aerogel by hydrolyzing the siloxane and polycondensing it with silica aerogel.

[0013] Furthermore, the amount ratio of the γ-aminopropyltriethoxysilane, succinic anhydride, N,N-dimethylformamide, the calcined silica aerogel and deionized water is 2-2.1g: 1-1.1g: 50mL: 0.8-1g: 2mL; the calcined silica aerogel is obtained by calcining the silica aerogel at a temperature of 500-550°C for 3-4h. Under high temperature calcination, the number of hydroxyl groups on the surface of the silica aerogel increases significantly, which is conducive to the subsequent condensation connection with the carboxyl-containing siloxane.

[0014] Furthermore, the aging temperature is 50-60° C., and the aging time is 2-4 hours.

[0015] Furthermore, the supercritical CO2 drying temperature is 30-45°C, the pressure is 6-8MPa, and the drying time is 3-5h.

[0016] A core-shell structure aerogel is prepared by the above preparation method.

[0017] Application of a core-shell structure aerogel in refractory bricks comprises the following steps:

[0018] Step S1, soaking the core-shell aerogel in an organic solvent to allow the organic solvent to fully fill the pores of the core-shell aerogel, then adding a refractory brick raw material with a particle size of 0.05-0.2 mm and stirring for 30 minutes, and after a homogeneous phase without aerogel powder is formed, adding the remaining refractory brick raw material and stirring and mixing, and finally adding a bentonite solution and stirring for 30 minutes to obtain a refractory brick mixture;

[0019] Step S2, pouring the refractory brick mixture into a mold, molding it at a pressure of 70-90 MPa, and obtaining a refractory brick blank after demolding. The refractory brick blank is transferred into a kiln, calcined at a temperature of 1200-1300°C for 24 hours, and after cooling out of the kiln, an aerogel-modified refractory brick is obtained.

[0020] Furthermore, the mass percentages of the components in the refractory brick mixture are 0.5-3% of core-shell structure aerogel, 2.5-15% of organic solvent, 80-90% of refractory brick raw material and 2-7% of bentonite solution, and the sum of the mass percentages of the above components is 100%; the organic solvent is acetone or N-methylpyrrolidone; and the concentration of the bentonite solution is 3-8wt%.

[0021] Furthermore, the refractory brick raw material includes the following components in weight percentage: 70-80% bauxite, 10-15% silicon carbide, and the rest is made up to 100% with white mud; the refractory brick raw material with a particle size of 0.05-0.2mm accounts for 10-25% of the total mass.

[0022] Beneficial effects of the present invention:

[0023] The present invention firstly performs carboxyl modification on ordinary silica aerogel to obtain carboxyl modified silica aerogel, and then uses the carboxyl silica aerogel as a precursor and adopts the strategy of "Zr encapsulating Si" to prepare silica / zirconium dioxide composite aerogel with a high temperature resistant core-shell structure; compared with unmodified silica aerogel, the carboxyl silica aerogel as a precursor can uniformly and firmly adsorb zirconium hydroxide formed by hydrolyzing zirconium oxychloride, and by controlling the amount of the carboxyl silica aerogel, a zirconium dioxide gel is compositely formed on the framework of the silica aerogel, so that the obtained core-shell structure aerogel has more excellent heat resistance and thermal insulation performance, solves the problem of structural collapse and loss of thermal insulation performance of ordinary silica aerogel at high temperature, and solves the problem that traditional silica aerogel cannot be synchronously calcined at high temperature with refractory brick raw materials;

[0024] The present invention utilizes a sacrificial template method, uses an organic solvent to fill a core-shell structure aerogel, and then successfully mixes the lightweight core-shell structure aerogel with a refractory brick raw material of equivalent particle size through electrostatic adsorption, then adds a refractory brick raw material of the remaining particle size and mixes them evenly, and then uses a bentonite solution as a binder to bond the above materials together, and obtains a refractory brick after high-pressure pressing and high-temperature firing, thereby solving the problem that the aerogel is light and cannot be well integrated with the refractory brick raw material; in addition, by reasonably controlling the addition amount of the core-shell structure aerogel to 0.5-3% of the total amount of the refractory brick mixture, the obtained refractory brick has the characteristics of high strength, high temperature resistance and low thermal conductivity;

[0025] Compared with existing refractory bricks, the refractory bricks prepared by the present invention greatly improve their thermal insulation performance under limited strength loss, and have the dual special effects of thermal insulation and mechanical strength, breaking the problem that traditional low thermal conductivity refractory bricks cannot take both strength and thermal insulation into account. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The present invention will be further described below in conjunction with the accompanying drawings.

[0027] Figure 1 It is a physical picture of the refractory brick samples prepared in Example 6, Comparative Example 4 and Comparative Example 6 of the present invention. The physical object on the left side of the figure is the refractory brick sample prepared in Comparative Example 4, the physical object in the middle is the refractory brick sample prepared in Comparative Example 6, and the physical object on the right side is the refractory brick sample prepared in Example 6. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] This embodiment provides a core-shell structure aerogel, comprising the following steps:

[0031] Step A1, adding 20g of γ-aminopropyltriethoxysilane and 10g of succinic anhydride to 500mL of N,N-dimethylformamide, stirring and mixing, stirring and reacting for 8h at room temperature under nitrogen protection, then adding 8g of silica aerogel calcined at 500°C for 3h and 20mL of deionized water, stirring and dispersing, continuing to stir and react for 5h at room temperature, centrifugally separating, washing with anhydrous ethanol, and drying to obtain carboxylated silica aerogel;

[0032] Step A2, at room temperature, add 1g of zirconium oxychloride to 5g of 97% ethanol aqueous solution to completely hydrolyze into a uniform solution, then add 4g of carboxylated silica aerogel and stir for 2h to evenly disperse the silica aerogel, then add 0.5g of gelling agent to form a sol solution, and age it in a closed environment at a temperature of 50°C for 4h to obtain a wet gel, and then submerge the wet gel with n-hexane to replace the solvent of the wet gel, the replacement times are 3 times, and supercritical CO2 is dried at a temperature of 30°C and a pressure of 6MPa for 5h, and after crushing, a core-shell structure aerogel is obtained.

[0033] Example 2

[0034] This embodiment provides a core-shell structure aerogel, comprising the following steps:

[0035] Step A1, adding 20.5g of γ-aminopropyltriethoxysilane and 10.5g of succinic anhydride to 500mL of N,N-dimethylformamide, stirring and mixing, stirring and reacting for 9h at room temperature under nitrogen protection, then adding 9g of silica aerogel calcined at 520°C for 3.5h and 20mL of deionized water, stirring and dispersing, continuing to stir and react for 6h at room temperature, centrifuging, washing with anhydrous ethanol, and drying to obtain carboxylated silica aerogel;

[0036] Step A2, at room temperature, add 1g of zirconium oxychloride to 6g of 97% ethanol aqueous solution to completely hydrolyze into a uniform solution, then add 4.5g of carboxylated silica aerogel and stir for 6h to evenly disperse the silica aerogel, then add 0.8g of gelling agent to form a sol solution, and age it in a closed environment at a temperature of 55°C for 3h to obtain a wet gel, and then submerge the wet gel with n-hexane to replace the solvent of the wet gel, the replacement times are 4 times, and supercritical CO2 is dried at a temperature of 38°C and a pressure of 7MPa for 4h, and after crushing, a core-shell structure aerogel is obtained.

[0037] Example 3

[0038] This embodiment provides a core-shell structure aerogel, comprising the following steps:

[0039] Step A1, add 21g of γ-aminopropyltriethoxysilane and 11g of succinic anhydride to 500mL of N,N-dimethylformamide and stir to mix, stir and react for 10h at room temperature under nitrogen protection, then add 10g of silica aerogel calcined at 550°C for 4h and 20mL of deionized water and stir and disperse thoroughly, continue stirring and reacting at room temperature for 6h, centrifuge, wash with anhydrous ethanol, and dry to obtain carboxylated silica aerogel.

[0040] Step A2, at room temperature, add 1g of zirconium oxychloride to 6g of 97% ethanol aqueous solution to completely hydrolyze into a uniform solution, then add 5g of carboxylated silica aerogel and stir for 10h to evenly disperse the silica aerogel, then add 1g of gelling agent to form a sol solution, and age it in a closed environment at a temperature of 60°C for 2h to obtain a wet gel, and then submerge the wet gel with n-hexane to replace the solvent of the wet gel, the replacement times are 5 times, and supercritical CO2 drying is carried out at a temperature of 45°C and a pressure of 8MPa for 3h. After crushing, a core-shell structure aerogel is obtained.

[0041] Comparative Example 1

[0042] The difference between this comparative example and Example 3 is that the operation of step A1 is not performed, and in step A2, an equal amount of untreated silica aerogel is used to replace the carboxylated silica aerogel, and the other raw materials and steps are the same.

[0043] Comparative Example 2

[0044] The difference between this comparative example and Example 3 is that in step A2, the amount of carboxylated silica aerogel is adjusted to 3 g, and the amounts of other raw materials and steps are the same.

[0045] Comparative Example 3

[0046] The difference between this comparative example and Example 3 is that in step A2, the amount of carboxylated silica aerogel is adjusted to 6 g, and the amounts of other raw materials and steps are the same.

[0047] The specific surface area, average pore size and thermal conductivity of the aerogels obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were tested, and the results are shown in Table 1:

[0048] Table 1

[0049] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 <![CDATA[Specific surface area m 2 / g]]> 450 471 487 464 384 492 Average pore size nm 19.26 20.42 21.45 21.73 17.74 21.54 Thermal conductivity W / (m·K) 0.045 0.047 0.049 0.038 0.056 0.059 Applicable temperature ℃ 1300 1300 1300 900 1300 1100

[0050] It can be seen from the data in Table 1 that the addition of carboxylated silica aerogel can increase the specific surface area and pore structure of the core-shell structure aerogel; with the increase in the amount of carboxylated silica aerogel added, although the specific surface area and average pore size increase, the thermal conductivity of the core-shell structure increases instead. Therefore, it is necessary to control the amount of carboxylated silica aerogel to prevent a negative impact on the thermal insulation performance of the core-shell structure aerogel.

[0051] Example 4

[0052] This embodiment provides an application of a core-shell structure aerogel in refractory bricks, comprising the following steps:

[0053] Step S1, immersing 3 parts by weight of the core-shell aerogel prepared in Example 1 in 15 parts by weight of acetone, then adding 20 parts by weight of a refractory brick raw material with a particle size range of 0.05-0.2 mm and stirring for 30 minutes, after a homogeneous phase without aerogel powder is formed, adding 60 parts by weight of a refractory brick raw material with the remaining particle size and stirring for mixing, finally adding 2 parts by weight of a bentonite solution with a concentration of 8wt% and stirring for 30 minutes to obtain a refractory brick mixture; wherein the refractory brick raw material includes the following components in weight percentage: 70% bauxite, 10% silicon carbide, and 20% white mud;

[0054] Step S2, pouring the refractory brick mixture into a mold, molding it at a pressure of 70 MPa, and obtaining a refractory brick blank after demolding. The refractory brick blank is transferred into a kiln, calcined at a temperature of 1200° C. for 24 hours, and cooled after being taken out of the kiln to obtain an aerogel-modified refractory brick.

[0055] Example 5

[0056] This embodiment provides an application of a core-shell structure aerogel in refractory bricks, comprising the following steps:

[0057] Step S1, adding 1.8 parts by weight of the core-shell aerogel prepared in Example 2 into 8.2 parts by weight of N-methylpyrrolidone and soaking them, then adding 17 parts by weight of refractory brick raw materials with a particle size range of 0.05-0.15 mm and stirring them thoroughly for 30 minutes, and after the homogeneous phase is in a state of aerogel-free powder, adding 68 parts by weight of refractory brick raw materials with the remaining particle size and stirring them thoroughly, and finally adding 5 parts by weight of a 6wt% bentonite solution and stirring for 30 minutes to obtain a refractory brick mixture; wherein the refractory brick raw materials include the following weight percentage components: 75% bauxite, 12% silicon carbide, and 13% white mud;

[0058] Step S2, pouring the refractory brick mixture into a mold, molding it at a pressure of 80 MPa, and obtaining a refractory brick blank after demolding. The refractory brick blank is transferred into a kiln, calcined at a temperature of 1250° C. for 24 hours, and after cooling out of the kiln, an aerogel-modified refractory brick is obtained.

[0059] Example 6

[0060] This embodiment provides an application of a core-shell structure aerogel in refractory bricks, comprising the following steps:

[0061] Step S1, adding 0.5 parts by weight of the core-shell aerogel prepared in Example 3 to 2.5 parts by weight of acetone and soaking it, then adding 9 parts by weight of refractory brick raw materials with a particle size range of 0.05-0.08 mm and stirring it for 30 minutes, after it becomes a homogeneous phase without aerogel powder, adding 81 parts by weight of refractory brick raw materials with the remaining particle size and stirring them, finally adding 7 parts by weight of a 3wt% bentonite solution and stirring for 30 minutes to obtain a refractory brick mixture; wherein the refractory brick raw materials include the following weight percentage components: 80% bauxite, 15% silicon carbide, and 5% white mud;

[0062] Step S2, pouring the refractory brick mixture into a mold, molding it under a pressure of 90MPa, and obtaining a refractory brick blank after demoulding. The refractory brick blank is transferred into a kiln, calcined at a temperature of 1300°C for 24h, and cooled after being taken out of the kiln to obtain an aerogel-modified refractory brick, such as Figure 1 Actual object shown on the right.

[0063] Comparative Example 4

[0064] The difference between this comparative example and Example 6 is that the core-shell aerogel prepared in Example 3 is not added in step S1, and the other raw materials and steps are the same. Figure 1 The actual object is shown on the left.

[0065] Comparative Example 5

[0066] The difference between this comparative example and Example 6 is that acetone is not used for soaking in step S1, and the core-shell structure aerogel prepared in Example 3 is directly mixed with the refractory brick raw material of the corresponding particle size, and the other steps are the same.

[0067] Comparative Example 6

[0068] The difference between this comparative example and Example 6 is that in step S1, the amount of the core-shell aerogel prepared in Example 3 is increased to 5.2 parts by weight, and the other raw materials and steps are the same, such as Figure 1 The actual object in the middle is shown.

[0069] According to GB / T 5072-2008 standard, the bulk density, porosity, compressive strength, refractoriness under load and thermal conductivity of the refractory bricks prepared in Example 4 to Example 6 and Comparative Example 4 to Comparative Example 6 were tested. Each group of refractory bricks was placed in a reburning furnace and kept warm at 1200° C. for 120 min. After the insulation was completed, the temperature of each group of refractory bricks was measured immediately. The test results are shown in Table 2:

[0070] Table 2

[0071]

[0072] It can be seen from the data in Table 2 that the refractory bricks prepared in Examples 4 to 6 exhibit higher compressive strength and lower thermal conductivity, and have the characteristics of high strength, high temperature resistance and low thermal conductivity; Figure 1 It can be seen that compared with Example 6, Example 6 uses an excessive amount (about 5% of the total amount of the refractory brick mixture) of core-shell structure aerogel, which leads to an increase in the porosity of the refractory brick and a significant decrease in the compressive strength. Therefore, it is necessary to strictly control the amount of core-shell structure aerogel within the scope of the present invention.

[0073] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0074] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a core-shell aerogel, characterized in that: The following steps are involved: Zirconium oxychloride is added to an ethanol aqueous solution for hydrolysis at room temperature, and then carboxylated silica aerogel is added and stirred for 2-10 hours, and then a gelling agent is added to form a sol solution. After sealed aging, a wet gel is obtained, and then the wet gel is solvent-displaced with n-hexane for 3-5 times. The wet gel is dried with supercritical CO2 and crushed to obtain a core-shell structure aerogel.

2. The method for preparing a core-shell aerogel according to claim 1, characterized in that: The mass ratio of the zirconium oxychloride, ethanol aqueous solution, carboxylated silica aerogel and gelling agent is 1:5-6:4-5:0.5-1; the concentration of the ethanol aqueous solution is 97wt%; and the gelling agent is propylene oxide or citric acid.

3. The method for preparing a core-shell aerogel according to claim 1, characterized in that: The carboxylated silica aerogel is prepared by the following steps: γ-Aminopropyltriethoxysilane and succinic anhydride are added to N,N-dimethylformamide and stirred to mix. The mixture is stirred to react for 8-10 hours at room temperature under nitrogen protection. Then, the calcined silica aerogel and deionized water are added and stirred to disperse. The mixture is stirred to react for 5-6 hours at room temperature. After centrifugal separation, washing with anhydrous ethanol and drying, carboxylated silica aerogel is obtained.

4. The method for preparing a core-shell aerogel according to claim 3, characterized in that: The dosage ratio of the γ-aminopropyltriethoxysilane, succinic anhydride, N,N-dimethylformamide, the calcined silica aerogel and deionized water is 2-2.1g:1-1.1g:50mL:0.8-1g:2mL; the calcined silica aerogel is obtained by calcining the silica aerogel at a temperature of 500-550°C for 3-4h.

5. The method for preparing a core-shell aerogel according to claim 3, characterized in that: The aging temperature is 50-60° C., and the aging time is 2-4 hours.

6. The method for preparing a core-shell aerogel according to claim 3, characterized in that: The supercritical CO2 drying process has a temperature of 30-45°C, a pressure of 6-8 MPa, and a drying time of 3-5 hours.

7. A core-shell aerogel, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.

8. The use of a core-shell structure aerogel in refractory bricks according to claim 7, characterized in that: The following steps are involved: Step S1, adding the core-shell structure aerogel into an organic solvent and soaking it, then adding a refractory brick raw material with a particle size of 0.05-0.2 mm and stirring and mixing it evenly, then adding the remaining refractory brick raw material and stirring and mixing it evenly, and finally adding the bentonite solution and continuing to stir and mix it evenly to obtain a refractory brick mixture; Step S2, pouring the refractory brick mixture into a mold, molding it at a pressure of 70-90MPa, and obtaining a refractory brick blank after demoulding. The refractory brick blank is transferred into a kiln, calcined at a temperature of 1200-1300°C for 24 hours, and obtained a refractory brick after cooling down from the kiln.

9. The use of a core-shell structure aerogel in refractory bricks according to claim 8, characterized in that: The mass percentages of the components in the refractory brick mixture are 0.5-3% of core-shell aerogel, 2.5-15% of organic solvent, 80-90% of refractory brick raw materials and 2-7% of bentonite solution; the organic solvent is acetone or N-methylpyrrolidone; and the concentration of the bentonite solution is 3-8wt%.

10. The use of a core-shell structure aerogel in refractory bricks according to claim 8, characterized in that: The refractory brick raw material comprises the following components in weight percentage: 70-80% bauxite, 10-15% silicon carbide, and the rest is supplemented with white mud to 100%; the refractory brick raw material with a particle size of 0.05-0.2mm accounts for 10-25% of the total mass.

Citation Information

Patent Citations

  • Preparation method of low-thermal-conductivity aluminum-silicon porous structure refractory brick

    CN116803956A

  • Novel spinel brick for rotary cement kiln

    CN211977551U

  • Preparation method of zirconium oxide-silicon oxide composite aerogel

    CN103214034A

  • Preparation method of high-temperature-resistant modified ZrO2-SiO2 composite aerogel

    CN115784242A

  • Carboxylic acid modified silicon dioxide aerogel, preparation method and application thereof, and drug delivery system

    CN116462202A

Cited By

  • Wave-absorbing core-shell structure super-surface composite material for unmanned aerial vehicle and preparation method thereof

    CN120757395A